Ethnobotany and phytochemistry of plants used to treat musculoskeletal disorders among Skaw Karen, Thailand - Rapeeporn Kantasrila; Hataichanok Pandith; Henrik Balslev; Prasit Wangpakapattanawong; Prateep Panyadee; Angkhana Inta (Taylor & Francis Group, 2024)
AbstractContext Musculoskeletal system disorders (MSD) are prevalent around the world affecting the health of people, especially farmers who work hard in the field. Karen farmers use many medicinal plants to treat MSD.Objective This study collects traditional plant-based remedies used by the Skaw Karen to treat MSD and evaluates their active phytochemical compounds.Materials and methods The ethnobotanical study was conducted in six Karen villages in Chiang Mai province using semi-structured interviews were of 120 informants. The data were analyzed using ethnobotanical indices including use values (UV), choice value (CV), and informant consensus factor (ICF). Consequently, the 20 most important species, according to the indices, were selected for phytochemical analysis using LC-MS/MS.Results A total of 3731 use reports were obtained for 139 species used in MSD treatment. The most common ailments treated with those plants were muscular pain. A total of 172 high-potential active compounds for MSD treatment were identified. Most of them were flavonoids, terpenoids, alkaloids, and steroids. The prevalent phytochemical compounds related to treat MSD were 9-hydroxycalabaxanthone, dihydrovaltrate, morroniside, isoacteoside, lithocholic acid, pomiferin, cucurbitacin E, leonuriside A, liriodendrin, and physalin E. Sambucus javanica Reinw. ex Blume (Adoxaceae), Betula alnoides Buch.-Ham. ex D.Don (Betulaceae), Blumea balsamifera (L.) DC. (Asteraceae), Plantago major L. (Plantaginaceae) and Flacourtia jangomas (Lour.) Raeusch. (Salicaceae) all had high ethnobotanical index values and many active compounds.Discussion and conclusions This study provides valuable information, demonstrating low-cost medicine plants that are locally available. It is a choice of treatment for people living in remote areas.